BNPT's Strategy In Anticipating Terrorism Crimes Through Cross-Sectoral Cooperation Synergy In Indonesia - Darmawan Sutawijaya (International Journal of Social Service and Research, 2023)
The development of global terrorist crimes has shown a significant increase in mode, quantity and quality, with Indonesia becoming one of the targets of terrorism. It was revealed that the local militant network had links to international networks. Terrorist activities utilize ideology and religion as tools to influence society and achieve their goals. Therefore, the Indonesian government faces the phenomenon of terrorism wisely, analyzing various aspects of national life to fight terrorism together with the international community. Terrorism aims to create fear and uncertainty, create panic, disrupt social stability and disrupt the relationship between society and government. Terrorism, both on an international and local scale, can hamper efforts to create a conducive investment climate within the country. Serious challenges arise from the failure of several key terrorist figures to be caught and the emergence of new forms of terrorist acts. Factors such as individual and group interests, social inequality, religious beliefs, injustice in law enforcement, and socio-cultural changes influence the development of terrorism. Countering terrorism requires a synergistic cross-sectoral cooperation strategy to create domestic security stability. Even though efforts have been made to deal with terrorism, public awareness of the dangers of terrorism is still weak. Effective strategies in anticipating terrorism include steps that support aggressive and diversified strategies, including increasing community resilience, revising laws, as well as deradicalization and communal rehabilitation programs. In a global context, terrorism has become a serious focus for countries around the world and is a UN program in its efforts to prevent and overcome it. The history of terrorism in Indonesia records an increase in the number and impact of acts of terrorism, including incidents such as the Bali Bombing, the JW Marriott hotel explosion, and the attack in front of the Australian Embassy Building. Joint efforts to confront and prevent terrorism in Indonesia must take into account regional characteristics, potential and influencing aspects, without sacrificing national interests and ethnic and religious sensitivities.